The Handbook of alternative investment strategies (Institutional Investor New York, 1999)
The Handbook of Alternative Investment Strategies brings you strategic insights and practical research on institutional investments in a range of alternative asset classes by the most successful practitioners and leading applied academics. In a single volume of over 300 pages, The Handbook of Alternative Investment Strategies is your complete guide to portfolio techniques, asset allocation, performance measurement and product selection in a range of assets including: hedge funds, managed futures, derivatives, private equity and venture capital, oil ; gas, energy futures, and more. It's the latest thinking by the leading experts that you need to know to make informed decisions on investing and avoid pitfalls in illiquid, high-risk investments. This book is a must-read for all senior-level investment decision-makers, including: Hedge Fund Managers, Portfolio Managers, Corporate Plan Sponsors, Family Office Executives, Insurance Company Executives, Institutional Salespersons and Consultants, and Chief Investment Officers.